The United States and the State of Israel - Schoenbaum, David (OUP E-Books., 1993)
Schoenbaum's book is a history of one of the most remarkable liaisons in international experience, a portrait of the special relationship between the last remaining superpower and the tiny Jewish state between the Jordan and the Mediterranean, and a study of how that relationship grew and works. From Truman to Bush, the United States has assured Israel's existence, while providing billions in military and economic support. Over the same period, no U.S. president has ever submitted a formal treaty of alliance to the Senate, or even moved the American embassy from Tel Aviv to Jerusalem. In fact.